Introducing molecular biology to medical physicists - Kwan, Hoong Ng; Chau, De Ming; Ramasamy, Thamil Selvee (International Organisation of Medical Physics, 2020)
Molecular biology helps us understand how genetic information is converted to functional proteins, how proteins interact through complex networks to determine the fate and function of a cell and how mutations lead to diseases. In the era of molecular medicine and ommissionin medicine, medical physicists need to acquire basic knowledge of molecular biology in order to communicate and collaborate with clinical and life science colleagues. This article documents our experience in introducing molecular biology as an academic module in a regional training course for educators held in Kuala Lumpur, Nov 2019. The module consists of didactic lectures, simulation, group exercises, etc. From the positive feedbacks that we received, the participants benefited from the exposure and we plan to produce some learning materials for future courses.